HFA-ICOS cardiovascular toxicity risk score validation in CARDIOTOX registry. (3rd October 2022) - Rivero Santana, B; Caro Codon, J; Juarez Olmos, V; Martinez Monzonis, A; Zatarain-Nicolas, E; Moliner, P; Cadenas Chamorro, R; Severo Sanchez, A; Valbuena Lopez, S; Zamora Aunon, P; Gomez Prieto, P; Gonzalez Juanatey, J R; et al.
Abstract: Background: Cancer therapy-related cardiovascular toxicity (CTox) is a growing medical problem and baseline cardiovascular (CV) risk assessment is recommended in all patients scheduled to receive potentially cardiotoxic cancer therapy. Based on literature review, the Heart Failure Association (HFA) Cardio-Oncology working group and the International Cardio-Oncology Society (ICOS) proposed a risk score to predict CTox but, it has not been validated. Purpose: To validate the HFA-ICOS anthracycline risk assessment score in the CARDIOTOX registry cohort (NCT02039622). Methods: The CARDIOTOX registry is a prospective multicenter study aiming at identifying factors related with CTox and assessing the utility of clinical, biochemical, and echo parameters for the early detection of CV disease during and after cancer therapy. A total of 1324 adult patients were prospectively included from April 2012 to October 2017. Data was collected at baseline, 3 weeks and 3, 6, 12, 18 and 24 months after initiation of treatment. Clinical follow-up was extended until January 2020. All patients receiving anthracycline chemotherapy were stratified according to HFA-ICOS risk score and Kaplan-Meier survival curves were analyzed to estimate the risk of all-cause mortality and anthracycline chemotherapy-related CV complications defined by HFA-ICOS risk score (left ventricular dysfunction (LVD), heart failure (HF) and arrhythmias). Results: A total of 1066 patients were included in the analysis. Baseline characteristics are summarized in table 1. 571 patients (53.6%) meet low, 333 (31.2%) medium, 152 (14.3%) high and 10 (0.9%) very-high HFA-ICOS CTox risk criteria. 197 patients (18.4%) died of any cause during follow-up. CV death occurred in 4 patients (2%), all caused by HF. Any degree of CTox was identified in 519 (48.7%) patients during the 110 months follow-up (73 (6.8%) developed clinical HF/HF hospitalization, 29 (2.7%) asymptomatic LVEF <50%; 27 (2.5%) clinically relevant arrhythmias and 390 (36.6%) an asymptomatic increase in cardiac biomarkers or a relative decrease in GLS>15%). Figures 1A and 1B showed the cumulative mortality rate and CTox rate during follow-up. CTox and all-cause mortality rates increased significantly according to the estimated baseline HFA-ICOS score. Conclusions: HFA-ICOS risk score categorizes patients according to their risk of developing anthracycline chemotherapy-related CTox, showing a good ability to predict both all-cause mortality and CTox. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Instituto de Salud Carlos III (PI13/00559).